HADIS-HADIS TENTANG JASA: WAKALAH, KAFALAH, HAWALAH(Telaah Sosiologis, Filosofis, dan Yuridis) - Mardiah Mardiah (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Islamic banking as part of the world of banking is a development of economic and financial concepts. This type of research uses qualitative methods by examining the juridical, sociological and philosophical legal basis relating to wakalah, kafalah and hawalah in the activities of Islamic finance company services. The results of this study indicate that the study of the legal basis regarding wakalah, kafalah and hawalah juridically, sociologically and philosophically both theoretically and practically, can be used for the activities of Islamic finance company services. This is supported by authentic hadiths, Compilation of Sharia Economic Law, opinions of (classical) Islamic scholars, fatwas of the MUI National Sharia Council (contemporary scholars) and regulations from the Financial Services Authority (OJK). In practice, this activity enforces mutual help for the sake of solidarity among people, so that they do not only seek profit but also receive benefits together